(3QSGdI aj af GdbHGfs ((3eUWai Hf eMeO GdHQgGfi s)
(3ChdgG (B:s
(3Ydjg JhcdJ hEdjg CfjH GdebOeI cd NW eSJbje LYd YehOkG eJSGhi GdZdX EPG JYdb ef efJUag hYdb HCMOgG ajg Kbd hHGdWQa GdBNQ Kbd BNQ hGdKbdGf eJSGhjGf cGdejRGf GdeYghO s
(3BNQgG (B:s
(3hJVY ajgG KbdkG HbOQ GdQjM Ke JYdb ai eSeGQ GdUZjQ KbdkG jMUd Hg GdJYGOd agh ebOGQ hRf bfXQI GdUZjQ hcPG JaYd HbfWQI GdcHjQ hPdc eG CQOfGg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdQjGVjGJs